Urinalysis in pediatrics patients in three Lima hospitals, 2011 - Morales-Del Pino, Jimmy Rinaldo (2012)
Objectives: To determine laboratory differences in procedures and results of urinalysis and microscopy in three Lima, Peru large hospitals. Design: Descriptive study, with non-probability sampling. Settings: Instituto Nacional de Salud del Niño, Hospital Docente Madre Niño San Bartolome, and Instituto Materno Perinatal, Lima, Peru. Materials: Pediatric patients’ urine samples. Interventions: Two hundred and eight urine samples were aliquoted and distributed to the three hospitals studied that used their own laboratory protocol. Urine tests results were collected and a survey on test procedures was performed. Results in each hospital were compared using kappa analysis test. Main outcome measures: Laboratory differences in procedures and results of urinalysis. Results: Survey revealed differences in the use of glass tubes, reaction times for urine test strips, speed centrifugation, power range and number of microscopic fields used to count elements. Agreement obtained for macroscopic analysis parameters for color and appearance were respectively fair (k=0.30) and slight (k=0.19); pH (k=0.26), leucoesterase (k=0.33) and blood (k=0.38) agreement in chemical analysis were fair. Finally, in microscopic analysis, agreement for leukocytes (k=0.63), erythrocytes (k=0.70) and calcium oxalate (k=0.66) were substantial; and for bacteria (k=0.08) and uric acid (k=0.34) were respectively slight and fair. Conclusions: Differences in procedures used for urine test processing among personnel of the three hospitals evaluated caused low agreement in results.